2020
DOI: 10.1101/2020.05.26.117143
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Local chromatin context dictates the genetic determinants of the heterochromatin spreading reaction

Abstract: Heterochromatin spreading, the expansion of gene-silencing structures from DNA-encoded nucleation sites, occurs in distinct chromatin contexts. Spreading re-establishes gene-poor constitutive heterochromatin every cell cycle, but also invades gene-rich euchromatin de novo to steer fate decisions.Unlike heterochromatin nucleation and assembly, the determinants of the spreading process remain poorly understood. Our heterochromatin spreading sensor separately records nucleation site-proximal, and distal, heteroch… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 109 publications
0
2
0
Order By: Relevance
“…In wild-type cells, Bre1 stimulates histone eviction at DSBs by H2B ubiquitination ( 123 ). Furthermore, a recent study analysing regulators of heterochromatin spreading in different chromatin contexts demonstrated that the HIRA histone chaperone and genes involved in HR pathway, such as rad50 and sfr1 , act in opposite ways ( 124 ). The authors detected these actions mainly at the ectopic heterochromatin domain composed of dh element embedded in gene-rich euchromatin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In wild-type cells, Bre1 stimulates histone eviction at DSBs by H2B ubiquitination ( 123 ). Furthermore, a recent study analysing regulators of heterochromatin spreading in different chromatin contexts demonstrated that the HIRA histone chaperone and genes involved in HR pathway, such as rad50 and sfr1 , act in opposite ways ( 124 ). The authors detected these actions mainly at the ectopic heterochromatin domain composed of dh element embedded in gene-rich euchromatin.…”
Section: Discussionmentioning
confidence: 99%
“…The authors detected these actions mainly at the ectopic heterochromatin domain composed of dh element embedded in gene-rich euchromatin. The HIRA complex has been implicated in heterochromatic domains expansion, while rad50 and sfr1 have been found to function in heterochromatin destabilisation ( 124 ). Consistently, we show that H3K9me2 nucleosomes are elevated in the dbl2Δ mutant at constitutive heterochromatic regions and LTRs (Figure 7D , E ).…”
Section: Discussionmentioning
confidence: 99%